Alpha Linolenic Acid-enriched Diacylglycerol Consumption Enhances Dietary Fat Oxidation in Healthy Subjects: A Randomized Double-blind Controlled Trial - Katsuragi, Yoshihisa; Saito, Shinichiro; Ando, Yasutoshi; Yamanaka, Nami; Ono, Takahiro; Suzuki, Chizuka; Osaki, Noriko (Journal of Oleo Science, 2017)
Consumption of alpha linolenic acid-enriched diacylglycerol (ALA-DAG) reduces visceral fat area. In this study, we performed a randomized, placebo-controlled, double-blind, crossover intervention trial to investigate the effect of ALA-DAG on dietary fat oxidation in comparison with control triacylglycerol (TAG). Each subject (n=16) consumed either 2.5 g/d of ALA-DAG or TAG for 14-d, separated by a 21-d washout period. At the end of each consumption period, we assessed dietary fat oxidation. ALA-DAG consumption significantly enhanced dietary fat utilization as energy compared to TAG consumption.